2016
DOI: 10.1007/s11270-016-2943-7
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Cu(II) from Water Samples Using Glycidyl Methacrylate-Based Polymer Functionalized with Diethylenetriamine Tetraacetic Acid: Investigation of Adsorption Characteristics

Abstract: A macroporous glycidyl methacrylate (GMA)-methylmethacrylate (MMA)-divinyl benzene ( D V B ) t e r p o l y m e r f u n c t i o n a l i z e d w i t h diethylenetriamine tetraacetic acid (DTTA) (GMA-MMA-DVB-DTTA) sorbent was successfully applied for the uptake of Cu(II) from the aqueous solutions. Adsorption characteristics for copper ion were investigated by a batch sorption in under different experimental conditions, and the optimum parameters for the quantitative sorption of Cu(II) ion were found to be as fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…The present research employed the most commonly utilized isotherm models, viz., Langmuir, D-R, and Freundlich in elucidating the adsorption phenomenon (Figure b–d). The mathematical expressions pertaining to these models are illustrated in Table . The findings demonstrated that, in comparison to the Freundlich and D-R models, the Langmuir model provided a better fitting ( R 2 = 0.9993).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The present research employed the most commonly utilized isotherm models, viz., Langmuir, D-R, and Freundlich in elucidating the adsorption phenomenon (Figure b–d). The mathematical expressions pertaining to these models are illustrated in Table . The findings demonstrated that, in comparison to the Freundlich and D-R models, the Langmuir model provided a better fitting ( R 2 = 0.9993).…”
Section: Resultsmentioning
confidence: 98%
“…The adsorption isotherms play a key role in describing how the adsorbent will interact with the adsorbate and providing insight into adsorption capacity. Their significance lies in understanding of the process of adsorption. Thus, the relationship between the adsorption capacity and the equilibrium concentration of TA on the polymer was illustrated by the adsorption isotherms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The developed method was also applied to the determination of Hg(II) and Cu(II) in water samples. According to the obtained results, the polymeric adsorbent was proposed as a promising adsorbent for the removal of target ions in contaminated water [39,40].…”
Section: Acrylic Polymers In Healthcarementioning
confidence: 99%